2012
DOI: 10.1210/en.2011-1527
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Suppression of Foxo1 and Foxo3 Causes Hypoglycemia and Hyperlipidemia in Mice

Abstract: Dysregulation of blood glucose and triglycerides are the major characteristics of type 2 diabetes mellitus. We sought to identify the mechanisms regulating blood glucose and lipid homeostasis. Cell-based studies established that the Foxo forkhead transcription factors Forkhead box O (Foxo)-1, Foxo3, and Foxo4 are inactivated by insulin via a phosphatidylinositol 3-kinase/Akt-dependent pathway, but the role of Foxo transcription factors in the liver in regulating nutrient metabolism is incompletely understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
192
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(200 citation statements)
references
References 58 publications
7
192
0
1
Order By: Relevance
“…Previous studies indicate that FOXO1 overexpression in the liver increased hepatic triacylglycerol content, owing to increased triacylglycerol synthesis [40,41], while recent studies suggest that FOXO proteins suppress hepatic lipogenesis and triacylglycerol levels [42,43]. In this study we show that overexpression of FOXQ1 decreases hepatic and serum triacylglycerol contents in db/db and DIO mice.…”
Section: Discussionsupporting
confidence: 49%
“…Previous studies indicate that FOXO1 overexpression in the liver increased hepatic triacylglycerol content, owing to increased triacylglycerol synthesis [40,41], while recent studies suggest that FOXO proteins suppress hepatic lipogenesis and triacylglycerol levels [42,43]. In this study we show that overexpression of FOXQ1 decreases hepatic and serum triacylglycerol contents in db/db and DIO mice.…”
Section: Discussionsupporting
confidence: 49%
“…Using a liver-specific deletion strategy, it has been shown that FoxO1, and not FoxO3/4, reduced blood glucose concentration both in normal and diabetic mice (34). Furthermore, the expression of FoxO1 in different tissues caused insulin resistance and glucose intolerance D) and Ad GFP for 24 h prior to incubation with LG or HG glucose for 24 h. A and C, total RNAs were prepared and used to detect catalase mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence staining of untreated liver tissues revealed a primarily nuclear expression pattern of FoxO3 (Fig. 3, A and D), suggesting that FoxO3 functions physiologically in normal liver homeostasis, probably in its ascribed role of lipid metabolism (40,41). Under oxidative stress, however, FoxO3 mainly translocates to the cytoplasm and membranes (Fig.…”
Section: ␤-Catenin-deficient Livers Exhibit Nuclear Retention Of Foxomentioning
confidence: 94%
“…6). Under homeostatic conditions, activation of FoxO3 is required for the control of cellular metabolism, including glycolysis (24) or fatty acid oxidation (40,41). Under oxidative stress, ␤-catenin signaling activates downstream SGK1 in wild-type hepatocytes, which inactivates FoxO3 by phosphorylation, leading to cytoplasmic translocation of FoxO3.…”
Section: ␤-Catenin Signaling Prevents Oxidative Stress-induced Liver mentioning
confidence: 99%